2010
DOI: 10.5012/bkcs.2010.31.02.442
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation of Adenosine 3',5'-Cyclic Monophosphate with β-Cyclodextrin: Kinetics and Mechanism by Ultrasonic Relaxation

Abstract: Adenosine 3',5'-cyclic monophosphate (cAMP) is a second messenger responsible for a multitude of cellular responses. In this study, we utilized β-cyclodextrin (β-CD) as an artificial receptor with a hydrophobic cavity to elucidate the inclusion kinetics of cAMP in a hydrophobic environment using the ultrasonic relaxation method. The results revealed that the interaction of cAMP with β-CD followed a single relaxation curve as a result of host-guest interactions. The inclusion of cAMP into the β-CD cavity was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The more hydrophobic the guest molecule is, the slower the dissociation from the host-guest complex is. The similar trends were found in the system with alcohols, AMP, cAMP, and amines as the guests [6][7][8]13] . These dependences of the rate constants on the hydrophobicity of the guest molecules reflect clearly on the stability of the inclusion complex.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The more hydrophobic the guest molecule is, the slower the dissociation from the host-guest complex is. The similar trends were found in the system with alcohols, AMP, cAMP, and amines as the guests [6][7][8]13] . These dependences of the rate constants on the hydrophobicity of the guest molecules reflect clearly on the stability of the inclusion complex.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, we demonstrated that the interaction reactions [6][7][8]13] . A comparison of the results of the dissociated form with those in the undissociated form declares that the rate constant for the ionized guest is smaller than that for the neutral guest.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation